“Assim cantava um cidadão do mundo”: dimensões da trajetória de Roberto das Neves - Braga, Francisco Victor Pereira (2022)
This thesis focuses on the trajectory of Roberto Barreto Pedroso das Neves (1907- 1981), a poet, intellectual and anarchist militant whose life is marked by outstanding sociopolitical activities in Portugal, Spain and Brazil, between the 1920s and 1970s. The study is organized in four chapters, in order to bundle multiple dimensions of Roberto das Neves militant trajectory, ideas and internationalist itinerary, considering anarchism, anti-fascism and Esperantism as facets of his libertarian thought and experience. The first chapter covers the time of his youth in Coimbra, in the 1920s, highlighting his passage through the Lyceum, his action among the students at the University of Coimbra, poetry and writing in the acratic press and the articulation in anarchist groups. It also discusses the clandestinity and the transits of Roberto das Neves between Portugal and Spain in the 1930s, the libertarian journalism in the matter of his writings, the action in the Spanish Revolution and the records of the action with the exiles of Salazarism and the refugees of the civil war in Spain. The second chapter addresses Roberto das Neves exile in Brazil, discussing the anti- fascist struggle in the experience of anarchist revolutionaries, militant intellectuals and exiled anti-Salazarist opponents. Specifically, the chapter focuses on the reconstitution of intellectual relations and elements of militant sociability in exile, from the resistance of anti-fascist nuclei, anarchist collectives and publishing groups, recovering writings in newspapers, books and other publications, participation in the anarchist press and the collaboration in periodicals of other political-ideological extractions. The third chapter deals with the publisher and the dissemination of the book, through Roberto das Neves activity at his Editora Germinal. The focus in this section is mainly on the repertoire of his readings, on his role as editor, on the bookstore activity, on the circulation of printed matter as a dimension of the anti- Salazarist struggle and on the clashes with censorship. Brief overview of the idea of an “international language”, records of the formation of the Esperantist movement and elements of Esperantism in its thinking and efforts to spread Esperanto.